Sensitivity of Fusarium graminearum to Carbendazim and Prochloraz - Dongfang, Ma; Shi, Huang; Peng, Zhang; Cai, Sun; Wendi, Huang; Guangjun, Li; Changqing, Zhang; Zhengwu, Fang (Plant Diseases and Pests(植物病虫害研究：英文版), 2017)
[ Objective] The paper was to understand the resistance of Fusarium graminearum to carbendazim and prochloraz in the main wheat producing areas in Hubei Province. [ Method] Totally 350 F. graminearum strains isolated in 2014 were determined to clear their sensitivity to carbendazim and prochloraz. [ Result] ALl isolates were sensitive to carbendazim and procidoraz in Hubei Province, and carbendazim was still valuable in controlling Fusarium head blight. The control effect of prochloraz was better than that of carbendazim, and the combination of prochloraz and carbendazim at the proportion of 1：7 received the best control effect. [ Conclusion ] Combination of chemical agents will occupy a more and more important position in future prevention and control against Fusarium head blight.